Identifying Professional Attributes and Behaviors of Healthcare Educators in Distance Learning Programs - Sadiq, Naushaba; Fatima, Fozia; Rauf, Ayesha; Fatima, Safia; Ayub, Rukhsana (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The main purpose of this study was to identify professional attributes and behaviors of healthcare educators in distance learning programs. A qualitative exploratory study was conducted. The population of this study was intended to consist of all students from a variety of locations and specialties in the certification program in health professions education (CHPE Fall-2020). There were 15 focus group discussions. Professional attribute and behaviors of healthcare educators based on their personal and social characteristics and actions. The prerequisite of an effective teacher was a part of the character of health care educators, and the teacher's personality is seen as a personal quality that lead to their obligations, topic expertise, pedagogical understanding, and dedication to change and continual improvement were all regarded as professional conduct of healthcare educators. Working interactions outside of the classroom, including social adaptability and flexibility, are regarded as social qualities and conduct of health care educators.